The Impact of Capability Maturity Model Integration on Return on Investment in IT Industry: An Exploratory Case Study - Saeed, A.; Afgun Usmani, R. S.; Akram, H.; Saqlain, S. M.; Ghani, A. (Engineering, Technology & Applied Science Research, 2017)
Capability Maturity Model Integration (CMMI) is a framework known for improving the quality of processes on consistent basis. This paper makes an attempt to explore, analyze and describe the impact of CMMI in terms of return on investment (ROI) for the IT industry. An IT organization who has acquired a maturity level of CMMI 2 is taken as case study. At first, in reference to the level of applied CMMI, a thorough study is completed. Afterwards the luxuries and limitations are studied and explored with reference to organizations applying the monetary terms using ROI framework. Finally, the presented research highlights the key benefits and difficulties in switching to CMMI from conventional quality assurance.